PENGUASA, PENGUSAHA, DAN PETANI: Kapitalisme Perkebunan Sawit, Distorsi Sosial Ekonomi, dan Perlawanan Petani di Indragiri Hulu, Riau, 1978–2010 - Zubir, Zaiyardam (Masyarakat Indonesia, 2018)
The main subject of this research is about the practice of modern capitalism in form of large scale of oil palm plantation and the peasant resistance in the Indragiri Hulu, Riau. It started from the government policy to expand non-oil and gas industry. The local government in Riau responded the policy by allowing big entrepreneurs to invest their capital in plantation economy, and the palm oil plantation was the main form. The main question raised in this study is why the peasant society in Indragiri Hulu resisted the practice of plantation economy in this area. This study employs historical method by using primary and secondary sources. The primary sources mainly derived through oral historical method and secondary source colleted from various libraries in Pekanbaru, Rengat, Yogyakarta, and Jakarta. The important finding of this research is that the expansion of plantation capitalism in Indragiri Hulu created various problems, especially land issues, as low ompensation and land grabbing. The authority and the businessmen also ignored local tradition related to land ownership like ulayat land, traditional arable forest and protected forest. This caused two form of resistant, closed and opened resistance. This research concludes that the practice of modern plantation based on traditional social and economic system triggered various anomalies They are includes: first, the weakening local community’s rights of land. Second, the violation of customry law by the capital owners especially those related to land. Third, the appearance of brokers that disadvantaged the peasant. Fourth, unbalanced relationships between the authority, the businessmen and peasant. Fifth, the emergence of peasant resistance against capitalism practice. Sixth, the rise of new sub-urban around the plantation.